American grill : a cookbook : 125 recipes for mastering live fire - Florence, Tyler (Abrams, 2024)
"In this ultimate grilling guide, the chef, bestselling author, restaurateur, and Food Network star embraces his love of live fire cooking to teach readers how to char, smoke, and slow-roast to perfection. Tyler Florence's 'American grill' is the outdoor authority for grill lovers everywhere, with techniques and recipes for upping your skill set and learning how to make perfect steaks, chops, fall-off-the-bone tender ribs, and more"--Page 4 of cover.